Grounding Falak Science: Assistance in Measuring Qibla Direction in Mosques in Agam Regency - Hendri; Elfiani; Nisa, Afdilla; Na’ali, Basri; Shafra (Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity was carried out on the basis of assistance because there are still pros and cons to the Qibla direction of the mosque at Syech Ahmad Chatib Islamic boarding school in Balai Gurah, Agam Regency and the need for community knowledge about Qibla direction that needs to be improved. Agam and the need for public knowledge about the direction of the Qibla that needs to be conveyed to the community both in the syech ahmad Chatib Islamic boarding school and the surrounding community. and the surrounding community. This mentoring training uses rashdul Qibla, theodolite and Qibla compass and by using discussion methods, demonstration and mentoring which is packaged in the form of hands-on training in the use of Qibla direction measuring device. Service that is packaged in the form of this training divided into 3 sessions, namely Providing material on Fiqh of Qibla direction, Problematics of Qibla Direction in Indonesia and continued with the practice of using the Qibla direction measuring device with theodilite and Qibla compass. Participants as many as 30 people who are Mosque Imama syech ahmad Chatib and students of the pesantren ahmad Chatib. In this activity, mosque imams were trained to understand the fiqh of the direction of Qibla direction as their basis in answering problems in the community about the the importance of facing the Qibla in terms of performing worship (prayer). Furthermore, the Imam of the mosque is then equipped with the practice of using theodolite tools and qibla compasses. and Qibla compass collaborated with the Qibla direction application.